2020
DOI: 10.1021/acs.jpcc.9b09803
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Nanoscale Supramolecular Structure, Effectiveness of Hydrogen Bonds, and Appearance of Debye Process

Abstract: Infrared and dielectric spectroscopy, X-ray diffraction, and density functional theory computations have been used to study the hydrogen-bonding pattern, molecular dynamics, internal structure, and dipole moment distribution in 2-ethyl-1-hexanol, 2-ethyl-1-hexylamine, 2-ethyl-1-hexanethiol, and 1-phenyl-2-butanol. Dielectric investigations revealed that Kirkwood–Fröhlich correlation factor is much larger or lower than the unity in the vicinity of the glass transition, dependent on the compound. It indicates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
2
9
0
Order By: Relevance
“…The obtained values agree well with E a of the dissociation process determined from the FTIR investigations. It is also worth adding that the presented spectroscopic results extend and complement the data published in the previous papers, creating a more thorough picture of the behavior of self-assembling alcohols during the dissociation process.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…The obtained values agree well with E a of the dissociation process determined from the FTIR investigations. It is also worth adding that the presented spectroscopic results extend and complement the data published in the previous papers, creating a more thorough picture of the behavior of self-assembling alcohols during the dissociation process.…”
Section: Introductionsupporting
confidence: 75%
“…Based on the literature data, one can conclude that both alcohols tend to form rather chainlike oligomeric selfassemblies consisted of around 10 molecules. 42,45 However, previous dielectric studies indicated that they differ in the value of the Kirkwood factor (g k ∼ 3 and g k ∼ 4 around T g for 2EHOH and nBOH, respectively 25,46 ), which defines the longdistance correlation between dipoles. It means that steric hindrance plays an important role and may affect the architecture of supramolecular associates as well as a chainring equilibrium in both alcohols.…”
Section: Resultsmentioning
confidence: 99%
“…Many simple as well as complex compounds possessing characteristic functional units, e.g., hydroxyl, amine, and thiol (H-bonded (HB) systems), or specific chemical motifs, such as long alkyl chains and aromatic moieties (van der Waals (vdW) materials), tend to self-assemble into supramolecular clusters that may organize themselves in domains obeying a few nanometers. Although this phenomenon, influencing basic physical properties of soft materials, water, or biological activity of proteins, is well-known and thoroughly studied, especially for binary and ternary mixtures, its nature is much less understood for single-component supercooled systems. It is directly related to the fact that, in contrast to the investigations carried out in solutions, there are only a few experimental methods capable of detecting and monitoring the self-association process in neat supercooled liquids.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it should be mentioned that one of the most useful tools dedicated to studying this phenomenon is X-ray diffraction (XRD). In the diffractograms collected for the systems creating supramolecular structures partially ordered on the nanoscale, except for the main diffraction peak connected to the short-range molecular order, also a “pre-peak” originating from the medium-range intermolecular correlations can be detected. ,,,, From the analysis of the position, width, shape, and intensity of this peak, together with the Fourier analysis of the total diffraction data in the form of the atomic pair distribution function, researchers may deliver important information about the size, range of order, geometry, and concentration of formed supramolecular associates/aggregates . Nevertheless, extensive studies on monohydroxy alcohols indicated that the analysis of the diffractograms even supported by the results of theoretical calculations (e.g., molecular dynamics and reverse Monte Carlo simulations) may lead to divergent conclusions and provide inconsistent information about the size of the supramolecular associates, their morphology, architecture, etc., even for the same compound. Therefore, to facilitate the diffraction data analysis, it is crucial to combine different information sources from various experimental and theoretical tools.…”
Section: Introductionmentioning
confidence: 99%
“…One can mention that the ability to form the hydrogen-bonded supramolecular structures is very weak in the case of thiol materials. However, it is true only for systems measured at room temperature, where these specific interactions are of comparable strength to the typical van der Waals forces. , At lower temperatures, this situation is much different since the thiol moiety is capable of creating stronger H-bonds that affect the structure and properties of the given system. Therefore, we expect that an increasing steric hindrance induced by the presence of an alkyl pendant group terminated by the H-bonding moiety might help us to better understand the puzzling dynamics of siloxane-based materials and properties of associating polymers , a new generation of systems intentionally designed to reveal noncovalent interactions, that is, H-bonding, metal–ligand bonding, π–π interactions, ionic bonding, and host–guest interactions .…”
Section: Introductionmentioning
confidence: 99%